Callose in leptoid cell walls of the moss Polytrichum and the evolution of callose synthase across bryophytes - Renzaglia, Karen; Duran, Emily; Sagwan-Barkdoll, Laxmi; Henry, Jason (Frontiers in Plant Science, 2024)
Leptoids, the food-conducting cells of polytrichaceous mosses, share key structural features with sieve elements in tracheophytes, including an elongated shape with oblique end walls containing modified plasmodesmata or pores. In tracheophytes, callose is instrumental in developing the pores in sieve elements that enable efficient photoassimilate transport. Aside from a few studies using aniline blue fluorescence that yielded confusing results, little is known about callose in moss leptoids. In this study on the moss Polytrichum, we investigated the location and abundance of callose during the development of leptoid cell walls using aniline blue fluorescence and quantitative immunogold labeling (label density) in the transmission electron microscope. We document the occurrence and increase of callose around plasmodesmata from meristematic cells to end walls in mature leptoids. We then compared the abundance of callose in hydrated stems to plants dried for 14 days under field conditions. Controlled drying resulted in a significant increase in label density around plasmodesmata and pores over counts in hydrated plants. This work verifies that callose is a crucial cell wall polymer around plasmodesmata from their inception to functioning in leptoids, and during water stress similar to sieve elements of tracheophytes. Because callose plays a role in key developmental and physiological processes in bryophytes, we conducted a bioinformatic study to assess the evolution of callose within and across bryophytes. We tallied published locations for this polymer and analyzed the phylogeny of callose synthase (CalS) genes for 46 bryophytes (24 mosses, 15 liverworts, and 7 hornworts) and one representative each of five tracheophyte groups. Three main clades (A, B, and C) of the CalS protein family were recovered. However, unlike seed plants, where the greatest diversity of homologs is found in clade A, the majority of gene duplication in bryophytes is in clade B. Among bryophytes, mosses exhibit the greatest number of multiple duplication events, while only two duplications are revealed in hornwort and none in liverworts. The absence in bryophytes of the CalS 7 gene that is essential for sieve pore development in angiosperms, reveals that a different gene is responsible for synthesizing the callose associated with leptoids in mosses.